The Impact of Academic Supervision on Teacher Pedagogical Competence and Teacher Performance: The Role Moderating by Teacher Efficacy - Singerin, Sarlota (International Journal of Elementary Education, 2021)
The success of the performance shown by the teacher is influenced by the surrounding environment, one of which is the role of the principal as a school supervisor. In addition, the quality of teacher performance can also be caused by the teacher's self-efficacy. This study aims to determine the effect of academic supervision on pedagogic competence and performance moderated by teacher efficacy. This research is a quantitative research that aims to determine the causal relationship between variables. The population in this study were all elementary school teachers with a sample involving 100 teachers who were selected by simple random sampling technique. Data collection in this study used a questionnaire distributed through the Google Form. The data collected was then analyzed by researchers assisted by the Smart PLS application. The results show that academic supervision has an effect on pedagogic competence with t-count >t-table (4.790> 1.984) and a P value < 5% (0.000 <0.05), academic supervision has an effect on teacher performance with t-count > t-table (4.344> 1.984) and a P value < 5% (0.000 <0.05), Efficacy was not able to moderate the effect of academic supervision on pedagogic competence with t-count < t-table (0.946 <1.984) and P value > 5% alpha standard (0.345> 0.05). Self-efficacy is able to moderate the effect of academic supervision on teacher performance with t-count > t-table (3.165> 1.984) and a P value < 5% (0.032 <0.05). Testing the moderating effect shows that efficacy is able to moderate the effect of supervision on teacher performance, while the pedagogical competence shows that efficacy has not been able to provide a significant moderating effect on pedagogic competence.